The novel SMYD3 inhibitor EM127 impairs DNA repair response to chemotherapy-induced DNA damage and reverses cancer chemoresistance - Paola Sanese; Katia De Marco; Martina Lepore Signorile; Francesca La Rocca; Giovanna Forte; Marialaura Latrofa; Candida Fasano; Vittoria Disciglio; Elisabetta Di Nicola; Antonino Pantaleo; Giusy Bianco; Vito Spilotro; et al. (Journal of Experimental & Clinical Cancer Research, 2024)
Abstract Background SMYD3 has been found implicated in cancer progression. Its overexpression correlates with cancer growth and invasion, especially in gastrointestinal tumors. SMYD3 transactivates multiple oncogenic mechanisms, favoring cancer development. Moreover, it was recently shown that SMYD3 is required for DNA restoration by promoting homologous recombination (HR) repair. Methods In cellulo and in vivo models were employed to investigate the role of SMYD3 in cancer chemoresistance. Analyses of SMYD3-KO cells, drug-resistant cancer cell lines, patients’ residual gastric or rectal tumors that were resected after neoadjuvant therapy and mice models were performed. In addition, the novel SMYD3 covalent inhibitor EM127 was used to evaluate the impact of manipulating SMYD3 activity on the sensitization of cancer cell lines, tumorspheres and cancer murine models to chemotherapeutics (CHTs). Results Here we report that SMYD3 mediates cancer cell sensitivity to CHTs. Indeed, cancer cells lacking SMYD3 functions showed increased responsiveness to CHTs, while restoring its expression promoted chemoresistance. Specifically, SMYD3 is essential for the repair of CHT-induced double-strand breaks as it methylates the upstream sensor ATM and allows HR cascade propagation through CHK2 and p53 phosphorylation, thereby promoting cancer cell survival. SMYD3 inhibition with the novel compound EM127 showed a synergistic effect with CHTs in colorectal, gastric, and breast cancer cells, tumorspheres, and preclinical colorectal cancer models. Conclusions Overall, our results show that targeting SMYD3 may be an effective therapeutic strategy to overcome chemoresistance.